2007
DOI: 10.1182/blood-2006-12-064444
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T lymphocytes carrying a pattern recognition protein Tag7 can detect evasive, HLA-negative but Hsp70-exposing tumor cells, thereby ensuring FasL/Fas-mediated contact killing

Abstract: Within the broad problem of host immune surveillance versus tumor immune evasion, a most intriguing question is how the cellular immunity can cope with cancerous cells that have gotten rid of the classical antigenpresenting machinery. One such option stems from (1) the fact that HLA loss is often attended with expression of Hsp70 on the tumor cell surface, and (2) our findings that human lymphocytes express a protein Tag7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
57
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 35 publications
8
57
0
2
Order By: Relevance
“…5,7 We have shown that Tag7 is expressed on the surface of CD4 C CD25 C lymphocytes, the highly specialized cells of the acquired immunity that participate in the killing of HLA-negative tumor cells by recognizing Hsp70 on their surface. 10,18 The latter protein is practically absent on the surface of normal cells but is exposed on tumor cells, thereby serving as an "alarm signal" for effector lymphocytes, and it is Tag7 that recognizes Hsp70 and makes a specific contact with it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,7 We have shown that Tag7 is expressed on the surface of CD4 C CD25 C lymphocytes, the highly specialized cells of the acquired immunity that participate in the killing of HLA-negative tumor cells by recognizing Hsp70 on their surface. 10,18 The latter protein is practically absent on the surface of normal cells but is exposed on tumor cells, thereby serving as an "alarm signal" for effector lymphocytes, and it is Tag7 that recognizes Hsp70 and makes a specific contact with it.…”
Section: Discussionmentioning
confidence: 99%
“…15 Moreover, the presence of this protein on the surface of highly specialized CD4 C CD25 C lymphocytes is absolutely required for their ability to recognize and subsequently kill HLA-negative tumor cells. 10 According to X-ray crystallographic data, the PGRP-S molecule has 2 binding sites: a highly conserved site for PNP binding and a more variable site for interaction with other ligands. 16 The latter may include proteins that form complexes with PGRP-S, and, importantly, such complexes can acquire new, and possibly opposing functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells, derived from hematological tumors, are devoid of the MHC antigen-presenting machinery, and are not recognized by the classical effectors of acquired immunity (CD8 ϩ CTLs). They are also totally insensitive to the soluble Tag7⅐Hsp70 complex (19). However, there is a specialized subset of CD4 ϩ CD25 ϩ LAKs with surface-exposed Tag7, which binds to Hsp70 exposed on the surface of approximately half of these HLA-negative tumor cells.…”
mentioning
confidence: 99%
“…Namely, a 6-day LAK culture, which does not contain natural killer (CD56) cells, is nonetheless capable of killing K562 and MOLT4 cells (18,19). These cells, derived from hematological tumors, are devoid of the MHC antigen-presenting machinery, and are not recognized by the classical effectors of acquired immunity (CD8 ϩ CTLs).…”
mentioning
confidence: 99%